Design of automatic control system on pakcoy plant parameters in nutrient film technique hydroponic media - Praptodiyono, Supriyanto; Saraswati, Irma; Kusuma, Sidiq Tri (Jurnal Teknika, 2024)
Technology in agriculture is always developing, one of which is cultivation using hydroponic media. One of the hydroponic cultivation techniques is the hydroponic nutrient film technique (NFT). The hydroponic cultivation of the nutrient film technique is carried out by placing plant roots in a shallow and circulating layer of water. One of the plants that can be used in NFT hydroponic media is the pakcoy mustard plant. During the growth period of pakcoy mustard in the hydroponic nutrient film technique media, parameters such as air temperature, water temperature, water level, water pH, and plant nutrients will greatly affect. The optimal air temperature during the growth of mustard greens is 22-33˚C, water temperature is 25-28˚C, water level is 25-35 cm or depending on the tank used, water pH is 6-7, and plant nutrition is 900-1400 PPM. If the parameter conditions in the hydroponic greenhouse are not in accordance with the optimal limits, the growth of the mustard greens will be stunted or die. In this study an automatic control system was designed using the WEMOS Mega 2560 microcontroller as the control center, DHT22 sensor, MAX6675 sensor, HC-SR04 ultrasonic sensor, PH-4502C sensor, analog TDS sensor, misting pump, peltier, water pump, and mini DC pump. . The results of this study are in the form of sensor reading values consisting of air temperature, water temperature, water level, water pH, and plant nutrients which have been transferred to the microcontroller so that they can be processed to be displayed on the LCD screen and if the sensor reading values do not match the optimal limits then the microcontroller will activate the misting pump, peltier, water pump, and mini DC pump automatically. With the automatic control system, the condition of these parameters can be maintained at optimal limits